Empirical study on East Asian economic integration. - Lee, Kang Siong. (2008)
There are renewed interests in East Asian regionlism. However, empirical evidence on the state of economic integration in this region is lacking. Through this research, the authors hope to assess the current nature and extent of integration between East Asian economics and address some relevant issues in this area.